Artificial intelligence in education : supporting learning through intelligent and socially informed technology - Looi, Chee-Kit (Frontiers in artificial intelligence and applications, 2005)
The field of Artificial Intelligence in Education includes research and researchers from many areas of technology and social science. This study aims to open opportunities for the cross-fertilization of information and ideas from researchers in the many fields that make up this interdisciplinary research area.